Is research in the social sciences and humanities heading in the right direction? - Ballon-Herrera, Carlos J. (2023)
Product of a post-rational vision and, therefore, apparently postmodern. Is the latter the central point, which prompts the question: how has this postmodern vision generated the increasing development of obscurantism, radical constructivism and relativism to the point of being filtered in academic spaces, reflecting today so much acceptance? That this work should not be understood as intolerance to freedom of expression, or a tendency towards scientific dogma, but rather, to problematize the correct path towards which work and academic life should be followed. Given what has been stated, it is proposed, -responding to the question of the topic that has been proposed- that indicated development it responds to a distorted and appropriate academic freedom to the needs of who expresses it, where the slogan; It is no longer how to approach understanding the world; rather, what is it that makes the academic decision and scientific and cultural production more viable for particularities.